2012
DOI: 10.1021/ja3016389
|View full text |Cite
|
Sign up to set email alerts
|

Interrogation of Global Active Site Occupancy of a Fungal Iterative Polyketide Synthase Reveals Strategies for Maintaining Biosynthetic Fidelity

Abstract: Nonreducing iterative polyketide synthases (NR-PKSs) are responsible for assembling the core of fungal aromatic natural products with diverse biological properties. Despite recent advances in the field, many mechanistic details of polyketide assembly by these megasynthases remain unknown. To expand our understanding of substrate loading, polyketide elongation, cyclization, and product release, active site occupancy and product output were explored by Fourier transform mass spectrometry using the norsolorinic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
88
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 46 publications
(96 citation statements)
references
References 49 publications
(150 reference statements)
8
88
0
Order By: Relevance
“…This change would require radical rerouting of the polyketide substrate chain to expose a carbon to the catalytic base that is distal (S type) or proximal (F type) to the phosphopantetheine thioester. As shown above and observed previously by others (1,29,36), in trans reconstitution of iPKSs from dissected domains incurs a penalty for catalysis in terms of product yield and/or fidelity. Thus, we elected to conduct these experiments with nrPKSs where the heterologous PT domains replace their native equivalents in cis (29).…”
Section: Resultssupporting
confidence: 72%
“…This change would require radical rerouting of the polyketide substrate chain to expose a carbon to the catalytic base that is distal (S type) or proximal (F type) to the phosphopantetheine thioester. As shown above and observed previously by others (1,29,36), in trans reconstitution of iPKSs from dissected domains incurs a penalty for catalysis in terms of product yield and/or fidelity. Thus, we elected to conduct these experiments with nrPKSs where the heterologous PT domains replace their native equivalents in cis (29).…”
Section: Resultssupporting
confidence: 72%
“…[21,22] Skiniotis and co-workers have presented a new model of PKSmediated natural compound synthesis based on moderate-resolution PikAIII data and biochemical studies. The new insight will change our view of PKSs.…”
Section: Integrity Of the Ks-at Unitmentioning
confidence: 99%
“…The conformation formed by SAT-KS-MAT and ACP domains was important for priming of hexanoyl groups and the number of condensation reactions of malonyl-CoAs to yield hexanoyl-primed octaketides. 39 In addition, TE/CLC was shown to have an editing role to cleave the thioesters of acetyl-ACP and hexanoyl-ACP, and decrease the amounts of derailment products derived from triketide intermediate. 39 Professor Hiroyuki Osada (RIKEN) presented the biosynthesis of reveromycin A (RM-A) and genetic engineering to produce various RM-A derivatives.…”
Section: Novel Transformations Expression Drug Discovery and Toolsmentioning
confidence: 99%
“…39 In addition, TE/CLC was shown to have an editing role to cleave the thioesters of acetyl-ACP and hexanoyl-ACP, and decrease the amounts of derailment products derived from triketide intermediate. 39 Professor Hiroyuki Osada (RIKEN) presented the biosynthesis of reveromycin A (RM-A) and genetic engineering to produce various RM-A derivatives. In vitro experiments showed that the post-PKS biosynthetic intermediates RM-A1a was converted to a dihydroketone intermediate by RevG, and the stereochemistry of the intermediate was controlled by RevJ, resulting in RM-A3a, which has a spiroacetal ring and shows 15S stereochemistry.…”
Section: Novel Transformations Expression Drug Discovery and Toolsmentioning
confidence: 99%